CHECKS AND BALANCES IN THE IMPEACHMENT MECHANISM OF THE PRESIDENT OR VICE PRESIDENT FROM A CONSTITUTIONAL LAW PERSPECTIVE - Salsabila, Safira; Suciana, Suciana; Indradjaja, Nobella; Chamdani, Chamdani (SYNTIFIC, 2024)
Background. There are changes to the mechanism following the amendment of the Indonesian 1945 Constitution, regarding the President's or Vice President's impeachment. After the amendment, the impeachment process can be initiated by the House of Representatives to the Constitutional Court by including strong allegations of violations committed by the President or Vice President. After that, the Constitutional Court will make a decision which will later be discussed in a parliamentary session of the People’s Consultative Assembly. Looking at the impeachment mechanism above, a new question arises as to whether this mechanism is by the supremacy of constitutional law. Research Method. This research is written to find the impeachment mechanism outlined in the 1945 Constitution according to the supremacy of constitutional law, by focusing on the function of checks and balances through qualitative methods. Findings. The results of this research show that the impeachment mechanism is not by the 1945 Constitution due to the existence of political mechanisms. Conclusion. The checks and balances process has not taken place in a balanced manner because the Constitutional Court's decision on the indictment is inexplicit or binding on both the People’s Consultative Assembly and the 1945 Constitution.